Cognitive Biases and Entrepreneurial Under-Diversification - Enrico Maria Cervellati; Pierpaolo Pattitoni; Marco Savioli (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2016)
Cognitive biases lead entrepreneurs to overinvest in their own companies, over exposing themselves to idiosyncratic risk. Our novel theoretical model explains entrepreneurial under-diversification by measuring the amount of potential bias in entrepreneurs' portfolio allocations brought about by overconfidence and over optimism. Simulation analyses based on our model allow us calculating the implicit levels of overconfidence and over optimism from observable portfolio choices. Finally, using a unique dataset including cross-regional data on Italian entrepreneurs and a structural equation modeling approach, we test the effect of overconfidence and over optimism on entrepreneurs' portfolio allocations. Consistent with our theoretical predictions, we find a positive relationship between overconfidence and entrepreneur investments in their own companies. On the other hand, the role of over optimism seems to be negligible.
Keywords: G02; G11; L26; 330